Ethical Teaching and the Social Justice Distraction. Issue 13 (December 2013) - Campbell, Elizabeth
This chapter presents a conceptual argument that positions two broad areas of educational scholarship—the moral and ethical dimensions of teaching and social justice education—as being quite separate, different, and ultimately antithetical, despite contemporary trends towards merging them in both theoretical and practical ways. It argues that an emerging tendency in social justice education to position its political agenda as a moral or ethical endeavor, especially within teacher education, is problematic in that it complicates, rather than enhances, the conceptualization of teaching as moral practice; it further distracts teachers and student teachers from fully engaging with the ethical aspects of their daily professional work.